Microsatellite-based parentage analysis of factorial crosses in Pacific oyster (Crassostrea gigas) larvae and spat - Taris, Nicolas; Sauvage, Christopher; Ernande, Bruno; Boudry, Pierre (97. Annu. Meeting of the National Shellfisheries Association, 2005)
Several studies have suggested that significant genetic variability might exist for some early developmental traits in the Pacific oyster, C. gigas. However, most studies have examined only limited numbers of families. More critically, these families were rarely replicated, leading to possible bias due to heterogeneous larval rearing conditions among families. To overcome these potential problems, we used a mixed-family approach with subsequent parentage analysis. A recently developed set of three multiplexed microsatellite markers was used to determine parentage in a complete factorial cross between 12 males and 4 females. Larvae were reared at two different temperatures (20 and 26°C) to provide a contrast resembling wild versus hatchery conditions. Samples were collected at the larval stage just before settlement and 2 months later. We observed significant male and female effects on larval growth and survival. More importantly, significant genotype x environment interactions were also observed for these traits. The potential selective pressures related to intensive rearing practices in commercial hatcheries will be discussed in the light of our findings.